(untitled) (Proceedings of Scientific Conference on Multidisciplinary Studies, 2024)
This article delves into the lexical-grammatical features of phrasal verbs in English and explores the challenges faced in accurately rendering them into Uzbek, highlighting the complexities of translation in capturing the intricacies of phrasal verb usage.